Pengaruh Kombinasi Metode Ceramah Dan Diskusi Peer Group Terhadap Pengetahuan Dan Sikap Tentang Personal Hygiene Saat Menstruasi Dalam Pencegahan Pruritus Vulvae Pada Remaja Putri Di MTs Al-Ikhlas Sukaluyu Tahun 2022 - Erni Amalia Utami; Nur Eni Lestari; Irma Herliana (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Adolescent girls during puberty will experience menstruation. If they cannot properly care for their reproductive organs during menstruation, it will cause several health problems, one of which is pruritus vulvae. Pruritus Vulvae occurs due to poor hygiene practices, to increase knowledge and attitudes of young women, researchers provide Lecture Methods and Peer Group Discussions about personal hygiene during menstruation in preventing Pruritus Vulvae.Objective: to see the effect of a combination of lecture methods and peer group discussions on knowledge and attitudes about personal hygiene during menstruation in preventing pruritus vulvae in young women at. Methods: and Peer Group Discussions about personal hygiene during menstruation in preventing Pruritus Vulvae.: The research design used was a quasy experiment. The analytical survey conducted in this study used the one group pre-test post-test approach design. The population is class VII students. Sampling was taken by purposive sampling, the sample size in this study was 30 young women. Data were collected using a questionnaire before and after being given the lecture method and peer group discussion of the knowledge instrument using the Guttman scale and the attitude instrument using the Likert scale and analyzed using the wilcoxon signed rank test. Result : The result of the study showed that the marginal homogeneity tes was obtained at knowledge p=0,000 and attitudes obtained a significant value p=0,003 in the post test. Suggestion : The lecture method and peer group discussion have a significant effect on the level of knowledge and attitudes of young women in preventing pruritus vulvae. The result showed that lecture methods and peer group discussions can be used us a means of health education to change health behavior for the better and can improve the hygiene of young women during menstruation in preventing pruritus vulvae.